Praia de Apeú-Salvador, município de Viseu, NE do Pará: ocorrência ou placer de minerais pesados - GONÇALVES, Bruno Leal (2019)
Heavy mineral is defined as a detrital mineral originated from an igneous rock, sedimentary or metamorphic after lithification, having specific gravity greater than 2.85 g/cm3 and commonly forming minor constituents or accessory minerals from rocks. The amount of heavy minerals in a given location depends on its abundance in the source area and the intensity of the transport process, which includes their ability to resistance to weathering, abrasion and its segregation due to differences in density and shape. Its occurrence in coastal and marine continental deposits inferring into account the evolution of these environments, highlighting as an important tool in sedimentology and stratigraphy. The origin and distribution trends contribute to the sedimentological and mineralogical characterization of the depositional environment, detailing aspects for each sedimentary environment. In oil exploration, they are used in the interpretation of environmental processes and the analysis of sedimentary basins. When found in concentrations higher than 1% in the fraction studied, it can be economically viable to exploit and then they are known as placer type deposits (residual placer, placer alluvial placers RIAO paleoplacer and offshore placers). Among placers highlight the economic value of ilmenite, rutile, zircon, monazite, magnetite, focusing on high-energy environments, after the breakdown of the source rocks. Work area is located in the geological context of the NE of Pará and Maranhão State NW, where it is included within the Craton and Gurupí Belt in this region are found mines of gold mining, hence the need for more detailed studies on species of minerals, their concentrations and their distribution areas. The APEU-Salvador beach, is located at the mouth of the Piriá estuary, that flows through the Gurupi and Arizona Groups, where exists some gold mines (garimpos). The sediments found in this beach are very fine sands, well selected, positive asymmetry will be negative. The main heavy minerals found in sediments were zircon, tourmaline, epidote, staurolite and kyanite with more abundant and less abundant garnet, chromite and cassiterite. Most have concentrations ranging up to 10% and is considered beach placer.